Investigation of the role of transporters on the hepatic elimination of an LAT1 selective inhibitor JPH203. Issue 9 (27th May 2013) - Toyoshima, Junko; Kusuhara, Hiroyuki; Wempe, Michael F.; Endou, Hitoshi; Sugiyama, Yuichi; Nakashima, Emi; Brouwer, Kim; Hammarlund‐Udenaes, Margareta; Terasaki, Tetsuya
Abstract JPH203 has been developed as an anticancer drug that inhibits L‐type amino acid transporter 1‐mediated essential amino acid uptake into tumor cells. This study sought to elucidate which drug transporters may be involved in JPH203 hepatic elimination, and to estimate human hepatic clearance. In Sprague–Dawley rats, JPH203 total body clearance approached blood flow rate. JPH203 biotransformation via phase II metabolism produces N‐acetyl‐JPH203 (NAc‐JPH203). NAc‐JPH203 accumulates in the bile, and NAc‐JPH203 canalicular efflux was significantly decreased in Mrp2‐deficient mutant rats (Eisai hyperbilirubinemic rats). JPH203 and NAc‐JPH203 are organic anion transporters [organic anion transporting polypeptide (OATP)1B1, OATP1B3, OATP2B1, and OAT3] substrates. In human cryopreserved hepatocytes, JPH203 uptake was saturable and inhibited by rifampicin, a prototypical OATP inhibitor. JPH203 metabolic clearance was larger than influx clearance and eventually passive clearance; JPH203 uptake appears to be the rate‐determining process in overall hepatic elimination. Furthermore, unlike rats, the human hepatic clearance was predicted to be intrinsic clearance rate limited. These results suggest that the hepatic uptake transporters are determinant factors to determine JPH203 systemic exposure. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:3228–3238, 2013